An assessment of the role of vinculin loss of function variants in inherited cardiomyopathy. Issue 9 (24th June 2020) - Hawley, Megan H.; Almontashiri, Naif; Biesecker, Leslie G.; Berger, Natalie; Chung, Wendy K.; Garcia, John; Grebe, Theresa A.; Kelly, Melissa A.; Lebo, Matthew S.; Macaya, Daniela; Mei, Hui; Platt, Julia; et al.
Abstract: The ACMG/AMP variant classification framework was intended for highly penetrant Mendelian conditions. While it is appreciated that clinically relevant variants exhibit a wide spectrum of penetrance, accurately assessing and expressing the pathogenicity of variants with lower penetrance can be challenging. The vinculin ( VCL ) gene illustrates these challenges. Model organism data provide evidence that loss of function of VCL may play a role in cardiomyopathy and aggregate case‐control studies suggest low penetrance. VCL loss of function variants, however, are rarely identified in affected probands and therefore there is a paucity of family studies clarifying the clinical significance of individual variants. This study, which aggregated data from >18, 000 individuals who underwent gene panel or exome testing for inherited cardiomyopathies, identified 32 probands with VCL loss‐of‐function variants and confirmed enrichment in probands with dilated cardiomyopathy (odds ratio [OR] = 9.01; confidence interval [CI] = 4.93–16.45). Our data revealed that the majority of these individuals (89.5%) had pediatric onset of disease. Family studies demonstrated that heterozygous loss of function of VCL alone is insufficient to cause cardiomyopathy but that these variants do contribute to disease risk. In conclusion, VCL loss‐of‐function variants should be reported in a diagnostic setting but need to be clearly distinguished as having lower penetrance.